The Association Between Cyclooxygenase-2 –1195G/A (rs689466) Gene Polymorphism and the Clinicopathology of Lung Cancer in the Japanese Population: A Case-Controlled Study - Sun , Rong; Tanino , Ryosuke; Tong , Xuexia; Isomura , Minoru; Chen , Li-Jun; Hotta , Takamasa; Okimoto , Tamio; Hamaguchi , Megumi; Hamaguchi , Shunichi; Taooka , Yasuyuki; Isobe , Takeshi; Tsubata, Yukari (Frontiers in Genetics, 2022)
The single nucleotide polymorphisms of COX-2 gene, also known as PTGS2, which encodes a pro-inflammatory factor cyclooxygenase-2, alter the risk of developing multiple tumors, but these findings are not consistent for lung cancer. We previously reported that the homozygous COX-2 –1195A genotype is associated with an increased risk for chronic obstructive pulmonary disease (COPD) in Japanese individuals. COPD is a significant risk factor for lung cancer due to genetic susceptibility to cigarette smoke. In this study, we investigated the association between COX-2 –1195G/A polymorphism and lung cancer susceptibility in the Japanese population. We evaluated the genotype distribution of COX-2 –1195G/A using a polymerase chain reaction-restriction fragment length polymorphism assay for 330 newly diagnosed patients with lung cancer and 162 healthy controls. Our results show that no relationship exists between the COX-2 –1195G/A polymorphism and the risk of developing lung cancer. However, compared to the control group, the homozygous COX-2 –1195A genotype increased the risk for lung squamous cell carcinoma (odds ratio = 2.902; 95% confidence interval, 1.171–7.195; p = 0.021), whereas no association is observed with the risk for adenocarcinoma. In addition, Kaplan-Meier analysis shows that the genotype distribution of homozygous COX-2 –1195A does not correlate with the overall survival of patients with lung squamous cell carcinoma. Thus, we conclude that the homozygous COX-2 –1195A genotype confers an increased risk for lung squamous cell carcinoma in Japanese individuals and could be used as a predictive factor for early detection of lung squamous cell carcinoma.